БРОНЗА ВА ИЛК ТЕМИР ДАВРИ ЧОРВАДОРЛАРИ ИШЛАБ ЧИҚАРИШ ХЎЖАЛИГИГА ДОИР АЙРИМ МУЛОҲАЗАЛАР (Scientific journal of the Fergana State University, 2023)
The article highlights some aspects of the production economy of the cattle-breeding population that invaded the southern and western territories of the Fergana Valley from the north-east of Central Asia, nicknamed the Kairakkum culture in science